Metafora Cinta dalam Novel Balada Cinta Majenun Karya Geidurrahman El-Mishry - Marsin Marsin; Ifan Iskandar; Siti Gomo Attas (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2019)
This study aims to describe the metaphor of love spoken by the main character in the novel Balada Cinta Maj Weaving by Geidurrahman El-Mishry using conceptual metaphors. The method used is descriptive analysis. The focus of the love metaphor is the expressions on the speech of the main character. Data collection uses documentation techniques with steps; read, mark, record, and categorize. Technical analysis uses content analysis that looks at the situation and condition of the speaker. The analysis shows that there are metaphorical expressions of love as an expression of the mental condition of the main character who is experiencing sadness, happiness, longing, and hope. Consequently sadness is the most dominant inner condition of hope, longing, and happiness. Conclusion, the whole phrase is used to convey the mental condition of the main character who is in love. Keywords: Metaphor, Conceptual, Love, Mental